Personality trait predictors of adjustment during the COVID pandemic among college students. - David C Rettew (Public Library of Science (PLoS), 2021)
Personality traits have been found to be related to a variety of health outcomes. The aim of this study was to examine how personality traits were associated with adjustment to the COVID pandemic in college students. The sample included 484 first-year university students (76% female) attending a northeastern university who completed the Big Five Inventory (BFI) personality assessment at the beginning of a semester that was disrupted by the COVID pandemic. Using a phone-based app, students completed daily ratings of mood, perceived stress levels, and engagement in a number of health promotion activities (exercise, mindfulness, adequate sleep, etc.) throughout the semester both before and after the onset of the pandemic (e.g., a within-person longitudinal design). Results, as expected, showed that mood and wellness indices generally declined during the COVID period, although stress levels actually decreased. Further, irrespective of COVID, improved mood, less perceived stress and greater participation in health promotion activities were significantly associated with a number of personality traits including neuroticism (lower), extraversion (higher), agreeableness (higher), and conscientiousness (higher). Of primary interest, mixed-effects models were used to test how major personality traits interacted with any changes in daily ratings from the pre-COVID to COVID period. Significant interactions terms were found suggesting differential impacts of the COVID epidemic for students with low versus high levels of particular traits. Higher levels of extraversion, for example, were found to be related to decreases in mood as the pandemic progressed in contrast to those with lower extraversion, for whom there was a slight increase in mood over time. These data support the conclusion that personality traits are related to mental health and can play a role in a person's ability to cope with major stressful events. Different traits may also be more adaptive to different types of stressors.